Prevalence of Burnout in Breast Imaging Radiologists. Issue 2 (28th February 2020) - Parikh, Jay R; Sun, Jia; Mainiero, Martha B
Abstract: Objective: Burnout is defined as a psychological syndrome arising as a response to chronic prolonged interpersonal job-related stress. Physician burnout has been increasingly recognized over the past decade as an epidemic within the United States. The goal of this study was to ascertain the prevalence of burnout amongst practicing breast imaging radiologists. Methods: A survey contained demographic questions based on workforce surveys carried out by the American College of Radiology and a validated condensed version of the Maslach Burnout Inventory (MBI) evaluating the three aspects of burnout. The radiologist members of the Society of Breast Imaging (SBI) received the survey internally from the SBI as a weekly e-mail with a web link to the survey from February 19, 2019, to March 13, 2019. The link allowed respondents to complete the survey anonymously. The authors were blinded to the SBI mailing list and the SBI was blinded to the responses. Results: A total of 370 breast imaging radiologists from the SBI responded to the survey. Overall, 290 out of 370 (78.4%) were highly burned out in at least 1 measured dimension of burnout; 197 out of 362 (54.4%) were highly burned out in at least 2 dimensions of burnout; and 27 out of 362 (7.5%) were highly burned out in all 3 dimensions of burnout. However, rates of personal accomplishment were high, with only 8.8% experiencing high burnout in the dimension of personal accomplishment. Conclusion: Our study demonstrates a high prevalence of burnout amongst breast imaging radiologists. Burnout rates were highest in the youngest breast imaging radiologists.